12=3u-u

Simple and best practice solution for 12=3u-u equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 12=3u-u equation:


Simplifying
12 = 3u + -1u

Combine like terms: 3u + -1u = 2u
12 = 2u

Solving
12 = 2u

Solving for variable 'u'.

Move all terms containing u to the left, all other terms to the right.

Add '-2u' to each side of the equation.
12 + -2u = 2u + -2u

Combine like terms: 2u + -2u = 0
12 + -2u = 0

Add '-12' to each side of the equation.
12 + -12 + -2u = 0 + -12

Combine like terms: 12 + -12 = 0
0 + -2u = 0 + -12
-2u = 0 + -12

Combine like terms: 0 + -12 = -12
-2u = -12

Divide each side by '-2'.
u = 6

Simplifying
u = 6

See similar equations:

| x-(2.5/100)x=51187500 | | (17+8)-6*2= | | 6x-10-6x=10 | | 5i-6x=(10y)i+10 | | 3mx=p+2n | | 12x-10-6x=10 | | 18s^2-48s-66=0 | | 10x+20y+8x-10y=48 | | 2i(7-i)= | | 9x+7y=-10 | | -3(k-18)+17=11 | | 5(x+3)+9=8x-3(x-3) | | 12n-5=4n+2 | | 6x+23=7 | | x-(2.5/100)x=408028750 | | 4x+2x+8=56 | | 4-2y-you=12 | | 9s^2+sforS=3 | | -113-3x=7x+37 | | 8u^2+8u+2=0 | | 9x-2x+49=28 | | x^2-8x-598=0 | | a^2+8a+26=5-2a | | 9(2r-5)-31/2(14r-8) | | 4(x+5)=9x+2-5x+18 | | -n/2=3 | | 3nl=5n-6z | | 6(a-4)+2=182 | | 1.5x+2.0y=572.5 | | 10+6x=3x+4 | | 2x-55=35+5x | | 5x-95=-4x+85 |

Equations solver categories